Mekanisme Good Corporate Governance terhadap Nilai Perusahaan yang Dimediasi Kualitas Laba dan Kinerja Keuangan - Imam Wahyudi; Umi Muawanah; Kohar Adi Setia (Jurnal Akuntansi dan Perpajakan, 2021)
This research aims to find out the effect of good corporate governance mechanism proxied on managerial share ownership, independent commissioners and independent audit committee toward firm value which is intervining earning quality and financial performance on manufactured company which recorded in Indonesia Stock Exchange. Be sided, it observed 39 companies in a year, furthermore there were 117 observed companies during 2015-2017. With using path analysis, it’s found that Good Corporate Governance is advantageous on profit quality, financial performance and firm value. However, earning quality has no significant effect on firm value while financial performance has on effect on firm value. indirect impact, earning quality and financial performance is not intervining between the influence of good corporate governance mechanism (managerial ownership, Independent commisioneees board and independent audit committee) toward the company value.